Neuropathic Pain Management: Prescription Strategies in a Tertiary Care Setting - Chethan Kumar JK; Jason Fernandes Jokem; Chandralekha N; Padmaja Udaykumar (National Board of Examinations Journal of Medical Sciences)
Background: Neuropathic pain, resulting from nerve damage, presents a complex challenge in clinical management due to its multifaceted nature and varied patient responses to treatment. Understanding prescription patterns in a tertiary care setting can provide insights into current clinical practices and highlight areas for improvement. Objective: prospective study of prescription pattern among neuropathic pain and its management. Methods: A prospective study was carried out with collecting patent data from a tertiary care Father muller medical college hospital, Mangalore, Karnataka. Where the data were collected from May 2023 to October 2023 and included patient demographic, diagnosis of neuropathic pain and prescription information. Statistical analysis of prescribing trends correlated to patient demographics was done using SPSS software. Results: The study analyzed 363 medical records, with a higher prevalence of male patients (56%) compared to female patients. Diabetic neuropathy was the most frequently observed condition, accounting for 49.04% of cases. The treatment and prescription patterns were based on the severity of pain, current condition, and age group of the patients. The age group most affected by neuropathic pain was 39-50 years. Monotherapy was administered to 40.77% of patients (148/363), with anticonvulsants being the most commonly prescribed drug class (76.2%). Conclusion: These findings demonstrate marked dependence on combination therapy and polypharmacy in managing neuropathic pain. While these strategies align with clinical guidelines, they also underscore the need for careful management to minimize the risks associated with multiple drug regimens. Future research should focus on optimizing treatment protocols and integrating non-pharmacological interventions to improve patient outcomes.